The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1517-869220192501178036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bcaa on Isometric Force Following Endurance Exercise in a Hot Environment

Abstract: Introduction: Fatigue due to endurance exercise results from both peripheral and central changes, and may influence subsequent performance during a strength task. The increase in serotonin concentration is one of the central factors associated with endurance exercise-induced fatigue, particularly in hot environments. A nutritional strategy employed to reduce serotonergic activation is supplementation with branched-chain amino acids (BCAA). Objective: To investigate whether BCAA supplementation attenuates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…According to the VAS pain [ 18 ] score table, the degree of muscle injury of each athlete is counted, as shown, as shown in Figure 8 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the VAS pain [ 18 ] score table, the degree of muscle injury of each athlete is counted, as shown, as shown in Figure 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding physical performance, T core has direct and indirect effects that limit the ability to exercise for prolonged periods (Cheung & Sleivert, 2004 ). For example, increased T core , possibly brain temperature, changes EEG activity (Nybo & Nielsen, 2001b ), increases perceived exertion (Nybo & Nielsen, 2001b ) and reduces the central drive for muscle contractions (Moraes et al., 2019 ; Nybo & Nielsen, 2001a ). Concerning the health of athletes, severe hyperthermia has been associated with impaired intestinal function (Pals et al., 1997 ; Pires et al., 2018 ), endotoxaemia (Gisolfi, 2000 ) and a higher incidence of heat stroke, the most severe heat illness (Armstrong et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of BCAAs on physical performance has been also tested in humans and results are quite paradoxical. Some studies have shown that BCAAs’ supplementation can reduce muscle damage and improve performance, ,, whereas other studies argued that the beneficial effect of BCAAs on physical exercise has not been observed in terms of muscle damage indices and performance . These controversial findings in human studies maybe attributed to the amount and duration of BCAA supplementation.…”
Section: Nutrients Supplementation Based On the Fatigue Generation Me...mentioning
confidence: 99%
“…Some studies have shown that BCAAs' supplementation can reduce muscle damage and improve performance, 53,55,56 whereas other studies argued that the beneficial effect of BCAAs on physical exercise has not been observed in terms of muscle damage indices and performance. 57 These controversial findings in human studies maybe attributed to the amount and duration of BCAA supplementation. This speculation is supported by a systematic review by Fouréand Bendahan, 58 which suggests that BCAA supplementation could be effective to ameliorate exercise-induced muscle damage if BCAA is given at least 1 week before the exercise for longer than 10 days at a daily dose of 200 mg/kg above.…”
Section: ■ Fatigue Causationmentioning
confidence: 99%